The use of Betel leaf in Nyirih tradition: Analyzing an ethnoscience-based learning material - Dedi Riyan Rizaldi; Yayuk Andayani; Aris Doyan; Muh. Makhrus; Ziadatul Fatimah; Eris Nurhayati (Universitas Ahmad Dahlan, 2021)
Nyirih tradition is one of popular traditions in Indonesia, a country with a diverse ethnic groups, cultures, and languages. The traditions are potential to be explored and used as contextual learning materials. This research aims to analyze the relationship between science (physics, biology, and chemistry) on the use of Betel leaf in the Nyirih tradition. This research used an ethnoscience approach, an approach which raises various cultures in a society to become a science learning topic, so that it would be easier for students to integrate various material in science learning with the real-life Â contexts. It was a qualitative research using the study literature type which consists of several steps, namely: (1) determining the topic, (2) gathering materials as references, (3) making an introduction, (4) determining the method, (5) discussing the findings, and (6) making a conclusion. The results suggest that the use of Betel leaf in Nyirih tradition could become an interesting topic in explaining several concepts in science.